Optimasi Suhu Aktivasi Proses Pembuatan Arang Aktif Limbah Tulang Kambing - Sari Wardani; Rina Mirdayanti (Fakultas Teknik, 2019)
Livestock waste, such as bone, has always been ineffectively exploited. Bones contain organic compounds that can be further processed into usable products such as charcoal and activated charcoal. This research, therefore, aims to identify the optimum temperature conditions suitable for the manufacturing process of activated charcoal from goat bone waste using thermal activation. The study uses a two-stage process which is carbonization and thermal activation. Activation temperatures used in the process were at a temperature of 500 °C, 600 °C and 700 °C for three hours. The results of the characteristics of activated charcoal thermally produced in this research met the Indonesian National Standard 06-3730-1995 about technical activated charcoal, and the optimum conditions were at an activation temperature of 500 °C. These characteristics include the values of the water content at 1.210%, ash content at 2.034%, absorption of iodine 926 mg/g, volatile matter of 0.434% and fixed carbon of 96.616%.